Sistem Penyimpanan dan Prosedur Temu Kembali Arsip Dinamis Aktif di kantor Sekretariat DPRD Provinsi Sumatera Barat - Rusdawati, Rusdawati; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
The purposes of this research are (1) to describe an active dynamic archive storage system at DPRD administration office of West Sumatra, (2) to describe the procedure of the information retrieval of the system. The data was collected descriptively by observation and interviewed to ward the archivists at the office. The findings of this research are as below. First, the archive storage system at DPRD secretary office in West Sumatra was unappropriate to the existing theories. In this office, the archive storage system only conducted based on the incoming and outgoing mails that caused the archieve being stacks, disorganized and difficult to retrieve. Second, the archieve retrieval system in the office was unappropriate because it was only done by using agenda which takes a long time to find the archive. The archivists have to manage the archieves one by one in the agenda based on the incoming and outgoing mails.Keywords: storage syste;retrieva;active dynamic archive